Physiological and performance effects of low- versus mixed-intensity rowing training - Ingham, S. A.; Carter, H.; Whyte, G. P.; Doust, J. H. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To examine the impact of low-intensity and a mixture of low- and high-intensity training on physiological and performance responses in rowing.